(untitled) (Communications in Computational Physics, 2020)
A numerical scheme capable of modeling fluid behavior on wetting surfaces is developed based on an interface-capturing lattice Boltzmann equation model [Q. Lou and Z. Guo, Phys. Rev. E 91, 013302 (2015)], which has not yet been applied to wetting problems. With the proposed numerical scheme, the spurious densities near the solid surfaces can be eliminated and a wide range of equilibrium contact angles can also be reproduced. Further, the equilibrium contact angle on the solid surface, as a simulation parameter, can be given in advance according to the wettability. Numerical tests, including the dynamics behavior of a liquid drop spreading on a smooth surface and the capillary intrusion, demonstrate that the proposed numerical scheme performs well and can eliminate the spurious densities near the solid surface.